PEMANFAATAN TEKNOLOGI COMPUTER VISION BERBASIS YOLO UNTUK MENDETEKSI KERUMUNAN DI SMKN 4 MALANG - Nugroho, Anan; Indaryanto, Faizal; Suni, Alfa Faridh; Arfriandi, Arief; Wibawanto, Hari; Oktaviyanti, Dwi; Savitri, Dina Wulung (Jurnal Abdi Insani, 2024)
In limited face-to-face learning, teachers and students must implement health protocols to prevent the spread of the Covid-19 virus. However, implementing health protocols in schools as a new habit in the midst of a pandemic is certainly not easy. There are many reports related to the number of violations of health protocols in schools during face-to-face learning. Therefore, by innovating and utilizing existing technology in the 4.0 era can help us to detect social boundaries. The purpose of this service activity is so that teachers and students can learn YOLO-based computer vision technology at SMKN 4 Malang as a means of preventing the spread of Covid-19. In addition, teachers and students can also learn to make simple applications based on YOLO. This activity begins with the socialization of YOLO-based computer vision technology as a crowd detection tool to the school. Then the design and manufacture of crowd detection tools by the service team, training in making crowd detection applications, and ending with a discussion between the trainees and the service team. The results of the service show that this activity has succeeded in developing a crowd detection tool that can help calculate the number and distance of people who do not apply health protocols at SMKN 4 Malang. This tool makes it easier for schools to monitor the activities of school residents in implementing health protocols. This service activity is very useful and in demand by teachers and students. This is evidenced by the enthusiasm of the participants in participating in the training of YOLO-based crowd detection tools.